Road salts as environmental constraints in urban pond food webs. - Robin J Van Meter; Christopher M Swan (PLoS ONE)
Freshwater salinization is an emerging environmental filter in urban aquatic ecosystems that receive chloride road salt runoff from vast expanses of impervious surface cover. Our study was designed to evaluate the effects of chloride contamination on urban stormwater pond food webs through changes in zooplankton community composition as well as density and biomass of primary producers and consumers. From May - July 2009, we employed a 2×2×2 full-factorial design to manipulate chloride concentration (low = 177 mg L(-1) Cl(-/)high = 1067 mg L(-1) Cl(-)), gray treefrog (Hyla versicolor) tadpoles (presence/absence) and source of stormwater pond algae and zooplankton inoculum (low conductance/high conductance urban ponds) in 40, 600-L mesocosms. Road salt did serve as a constraint on zooplankton community structure, driving community divergence between the low and high chloride treatments. Phytoplankton biomass (chlorophyll [a] µg L(-1)) in the mesocosms was significantly greater for the high conductance inoculum (P<0.001) and in the high chloride treatment (P = 0.046), whereas periphyton biomass was significantly lower in the high chloride treatment (P = 0.049). Gray treefrog tadpole time to metamorphosis did not vary significantly between treatments. However, mass at metamorphosis was greater among tadpoles that experienced a faster than average time to metamorphosis and exposure to high chloride concentrations (P = 0.039). Our results indicate differential susceptibility to chloride salts among algal resources and zooplankton taxa, and further suggest that road salts can act as a significant environmental constraint on urban stormwater pond communities.